The Role of the Tourism Sector in Improving the Local Community's Economy in the Moyo Island Tourism Village, Sumbawa Regency - Puput Nabila; Edi Irawan (Escalate : Economics and Business Journal, 2024)
Abstract:This study analyzes the role of the tourism sector in improving the local economy in Moyo Island Tourism Village, Sumbawa Regency, where tourist visits jumped from 256 (2021) to 4,690 people (2024) but local economic benefits are limited. The purpose of the study is to examine the influence of job providers (X1), MSME development (X2), and community empowerment (X3) on improving the local economy (Y). A quantitative correlational verification approach was used with a population of 533 people and a sample of 84 respondents through the Slovin formula. The Likert scale questionnaire instrument was tested for validity and reliability, analyzed by multiple linear regression with SPSS 25 after the classical assumption test. The results show that X1 (t = 3.548; sig = 0.001) and X3 (t = 2.176; sig = 0.033) have a significant partial effect, X2 is not significant (sig = 0.328), and simultaneously all three are significant (F = 21.089; sig = 0.000; R² = 44.3%).